Asynchronous programming with SwiftUI and Combine : functional programming to build UIs on Apple platforms - Friese, Peter (Apress, 2023)
Develop UI-heavy applications more easily, faster, and error-free. Based on several enhancements to the Swift language, SwiftUI takes a declarative approach to building UIs. Instead of imperatively coding the UI, this book will show you how to describe how you want your UI to look. SwiftUI treats the UI as a function of its state, thereby making managing your app's state a lot easier. Change the underlying data model to redraw all parts of the UI that are connected to that particular slice of data. Likewise, easily update the underlying data model from the UI elements your data model is connected to. Combine is Apple's Functional Reactive Programming framework. It complements SwiftUI and other frameworks, such as the networking APIs, in a natural way. Using Combine, you can subscribe to events and describe data processing in a way that is free of side effects. This allows for an easier implementation of event-driven applications. Using SwiftUI and Combine build more error-free apps in a shorter amount of time, targeting all of Apple's platforms (iOS, iPadOS, watchOS, macOS, tvOS) with little to no overhead. By the end of the book you will have a solid understanding for architecting and implementing UI-heavy apps in a declarative and functional reactive way using SwiftUI, Combine, and async/await.